The Effect Fe Tablets and Vitamin C with Fe Tablets and Strawberry Juice on Hb Adolescent Girls - Dewi Kurniati; Rini Kundaryanti; Ericha Septiani Rahayu (Nursing and Health Sciences Journal (NHSJ), 2021)
Anaemia affects about 23% of Indonesian adolescent girls. The red blood cell insufficiency affects 4.8 million adolescent girls out of a total population of roughly 21 million. So that arises due to a combination of poor dietary habits and a lack of physical exercise. The purpose of this research is to see whether there is a difference in the effects of giving Fe tablets and vitamin C with Fe tablets and strawberry juice. The study population was adolescent girls with a range of ages of 16-17 years. Then, the research design was quasi-experimental with two group pre-test and post-test designs. A sample was 30 adolescent girls. The sampling technique was purposive sampling. Statistical tests used paired t-tests and independent t-tests. The results of the study p-value = 0.014 < 0.05, so there was a significant influence between giving Fe tablets and vitamin C with Fe tablets and strawberry juice on adolescent girls. It is expected that the consumption of Fe tablets with vitamin C such as strawberry juice will increase the Hb level of adolescent girls.Keywords: Increased haemoglobin, adolescent girls, Fe tablets, vitamin C, strawberry juice